2012
DOI: 10.1097/jcp.0b013e31823f3b5f
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acid Augmentation of Citalopram Treatment for Patients With Major Depressive Disorder

Abstract: The objective of this study was to explore the efficacy of combination therapy with citalopram plus omega-3 fatty acids versus citalopram plus placebo (olive oil) in the initial treatment of individuals with Major Depressive Disorder (MDD). We hypothesized that combination therapy would not only lead to greater efficacy, but a more rapid onset of therapeutic response. Forty-two subjects participated in this nine week randomized, masked, placebo-controlled study of combination therapy (2 grams containing a blen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
150
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 33 publications
4
150
0
1
Order By: Relevance
“…Addition of both celecoxib (Akhondzadeh et al, 2009) and acetylsalicylic acid (which blocks COX-1 and COX-2) (Mendlewicz et al, 2006) augmented treatment responses to fluoxetine. Omega-3 fatty acids have increased the antidepressant efficacy of fluoxetine (Jazayeri et al, 2010) and citalopram (Gertsik et al, 2012), and a meta-analysis reported direct antidepressant effects when combining all sources of omega-3 fatty acids (e.g. docosahexaenoic acid, fish oils) (Lin and Su, 2007).…”
Section: Translational and Therapeutic Implicationsmentioning
confidence: 99%
“…Addition of both celecoxib (Akhondzadeh et al, 2009) and acetylsalicylic acid (which blocks COX-1 and COX-2) (Mendlewicz et al, 2006) augmented treatment responses to fluoxetine. Omega-3 fatty acids have increased the antidepressant efficacy of fluoxetine (Jazayeri et al, 2010) and citalopram (Gertsik et al, 2012), and a meta-analysis reported direct antidepressant effects when combining all sources of omega-3 fatty acids (e.g. docosahexaenoic acid, fish oils) (Lin and Su, 2007).…”
Section: Translational and Therapeutic Implicationsmentioning
confidence: 99%
“…Furthermore, PUFAs have the ability to modulate the expression, properties, and action of dopamine, serotonin, and ACh [79][80][81][82], especially during the perinatal period during which the growth and development of brain is at maximum and ACh, in turn, regulates release of PUFAs [83]. Thus, u-3 PUFAs and AA modulate neural function, including neurotransmission, membrane fluidity, ion channel, and enzyme regulation and gene expression, prevent inflammation, and thus, could be of significant benefit in the prevention and management of autism.…”
Section: Diffusion Tensor Imaging Magnetic Resonance Imaging and Autismmentioning
confidence: 99%
“…Several trials have been conducted in this context, however, meta-analyses reported mitigated outcomes so far [129,133]. Some trials showed no convincing effect while others demonstrated that ω-3 supplementation for 8-12 weeks have significant positive effects, notably because it improves the efficiency of antidepressants and thus increases the proportion of remission [134]. The lack of clear effect of ω-3 supplementation to treat mood and anxiety disorders in humans can be explained by the complexity of neuropsychiatric disorders and the heterogeneity of methods in the different studies.…”
Section: Pufas / Endocannabinoids Interactions In Mood and Anxiety DImentioning
confidence: 99%